Synthesis, photophysics, and photochemistry of peripherally Schiff base-zinc complex substituted zinc phthalocyanine - Sen, Pinar; Yildiz, S. Zeki; Atmaca, Goknur Yasa; Erdogmus, Ali (TAYLOR & FRANCIS LTD, 2018)
The content of this work is based on the introduction of the salicylhydrazone-zinc complexes into the phthalocyanine core. The reaction of the salicylhydrazone substituted ZnPc (1) with the related zinc(II) salt in basic conditions in DMF yielded bis[bis(salicyhydrazone)phenoxy)zinc(II)] phthalocyaninato zinc(II) (5) in which two salicylhydrazone-Zn complexes are linked through oxygen bridges to the macrocyclic core as three-nuclear complex. The novel compound synthesized in this study was fully characterized by general spectroscopic techniques such as FT-IR, UV-vis, H-1 NMR, C-13 NMR, elemental analysis and mass spectroscopy. In addition, spectral, photophysical (fluorescence quantum yields), and photochemical (generation of singlet oxygen and photo stability under light irradiation) properties of newly synthesized phthalocyanine (5) and the starting Pcs molecules used to obtain this molecule were investigated in DMSO solutions, comparatively. [GRAPHICS] .
Keywords: Synthesis; metallo phthalocyanine; schiff base; salicylhydrazone metal complex; fluorescence property; singlet oxygen; photodegradation; ZN(II); CU(II); SERIES; Chemistry